The Effect of E-commerce, Social Media and Digital payment on Increasing Revenue of Micro, Small and Medium Enterprises (MSMEs) in Mataram City - Aulia, Irma; Nurabiah, Nurabiah (International Journal of Business and Applied Economics, 2025)
This study examines the impact of e-commerce, social media, and digital payments on enhancing the revenue of Micro, Small, and Medium Enterprises (MSMEs) in Mataram City. These three variables were chosen because of their role in expanding markets, increasing customer interaction, and facilitating financial transactions. Data were gathered from 118 MSME participants via surveys and analyzed utilizing the Partial Least Squares (PLS) approach. The findings indicate that e-commerce, social media, and digital payment positively and significantly influence the income of MSMEs. Where E-commerce can support marketing efficiency, social media increases product visibility, and digital payments facilitate transactions and increase operational efficiency.